The Comparison of Auditory Selective Attention and Auditory Divided Attention between Patients with Cerebrovascular Accident and Normal Cases - Hossein Talebi; Seyyed Ali-Akbar Tahayi; Mohammad Akbari; Mohammad Kamali (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: Cerebrovascular Diseases (CVD) are one of the most important and common diseases that affect on Central Auditory System. In this research, we tried to assess auditory selective attention and auditory divided attention in patients with Cerebrovascular Accident within age range of 40-75 years old in respect to having no problems in peripheral auditory system. Materials & Methods: This cross-sectional Comparative study was conducted on 15 normal and 15 patients' cases with CVA that were selected with Purposive sampling and divided to two groups six patients with lesion in left hemisphere and nine with lesion in right hemisphere. In order to evaluation of auditory selective attention and auditory divided attention, Farsi versions of competing sentence test and dichotic digits test were used respectively. Results: There were significant differences between mean scores of CST in the patients with CVA and the normal group in some conditions (P<0/05). There were significant differences between mean scores of DDT in both ears of patients with CVA and normal group. Conclusion: In addition, these scores indicate that auditory divided attention is more susceptible to CVA than auditory selective attention. One may conclude that patients with CVA may show their hidden hearing loss or some difficulties in central auditory processing, especially in auditory attention.